Evaluation of genetic introgression from domesticated pigs into the Ryukyu wild boar population on Iriomote Island in Japan. (23rd April 2014) - Murakami, K.; Yoshikawa, S.; Konishi, S.; Ueno, Y.; Watanabe, S.; Mizoguchi, Y.
Summary We evaluated genetic introgression from domesticated pigs into the Ryukyu wild boar (RWB) population on Iriomote Island based on their genetic structure and diversity. We used a combination of mitochondrial DNA D‐loop region (596 bp) polymorphisms and 23 microsatellite markers. RWBs (n = 130) were collected from 18 locations on Iriomote Island and compared with 66 reference samples of European and Asian domestic pigs. We identified six distinct haplotypes, involving 22 single nucleotide polymorphisms (including one insertion) in the RWB population. The phylogenetic tree had two branches: the RWB group and domestic lineage. Fourteen of 130 RWBs (10.8%) belonged to the European domestic lineage, including 11 RWBs from the Panari Islands, northwest of Iriomote Main Island (IMI). The heterozygosity values, total number of alleles, number of effective alleles and polymorphism information content of the RWB groups were lower than those of the European domestic groups. The RWB population on IMI had a lower heterozygous deficiency index (FIS = 0.059) than did the other populations, which indicates that this population was more inbred. There was a large genetic distance (FST = 0.560) between RWBs on IMI and the Meishan populations. Structure analysis using the 23 microsatellite markers revealed that 16 RWBs had an admixture pattern between RWB and domesticated pig breeds. These results suggest that gene flow may have occurred from domestic pigs to RWBs and demonstrate that there was low genetic variation in the IMI population.